TEACHERS’ PERCEPTIONS ON THE USE OF GOOGLE CLASSROOM IN ENGLISH LEARNING AMID THE COVID-19 PANDEMIC IN MANDAU SUB-DISTRICT - Hilmer Marulitua Simatupang; Jismulatif Jismulatif; Dahnilsyah Dahnilsyah (International Journal of Educational Best Practices, 2022)
This research aimed to explore the teachers’ perceptions on the use of Google Classroom in English learning amid the COVID-19 pandemic in Mandau sub-district. There were 41 English 41 English teachers who have used Google Classroom from 8 public senior high schools chosen as samples. This study used a quantitative method that employed questionnaire to collect the data consisting of 20 statements. Using SPSS 25, the quantitative data were analyzed descriptively and inferentially. The results show that the use of Google Classroom is considered very helpful during the pandemic with mean value 4.28 (very high). In the learning process, the use of Google Classroom is considered very practical, showing the mean value 4.02 (high). In the teams of ease of learning, Google Classroom is considered easy to learn the features and uses with a mean value of 4.27 (very high). The teachers are satisfied with Google Classroom as indicated by the mean value of 4.29 (very high). Therefore, the teachers felt that using Google Classroom in online learning during the COVID-19 pandemic was effective because the application was a good way or alternative way to do the learning activity and made it easier to teach English during the COVID-19 pandemic.